Editorial: Recent advances in intelligent robotic systems. Issue 4 (26th April 2019) - Xu, Xin; Liu, Yong
Abstract : This Editorial introduces the motivation and organization process of the special issue on intelligent robotic systems. The major contributions of the six papers published in the special issue are discussed. In these papers, three papers present recent progresses in robot navigation and localization in complex environments. One paper reports a new robot sensing approach. The other two papers address the problems in robot dynamics modeling and service modeling in human‐robot interaction.